(untitled) (International Journal of Environmental Sciences, 2025)
The Olive Ridley turtle (Lepidochelys olivacea) is renowned for its mass nesting phenomenon, known as "arribada," wherein thousands of female turtles come ashore simultaneously to lay eggs. The Rushikulya rookery along Odisha’s coastline is one of the world’s most significant nesting sites, hosting nearly 50% of the global Olive Ridley population annually. Despite their ecological importance, these turtles face threats such as habitat destruction, bycatch in fisheries, climate change, and pollution, leading to their classification as "Vulnerable" by the International Union for Conservation of Nature (IUCN). Conservation efforts have traditionally relied on enforcement-driven approaches, including legal protections under the Wildlife Protection Act (1972) and site patrolling. However, these methods often lack meaningful community involvement, which is vital for sustainable conservation. This study explores participatory communication as a transformative strategy for Olive Ridley turtle conservation, emphasising collaboration, mutual understanding, and empowerment. By engaging local communities, volunteers, and forest officials through two-way communication and community-driven initiatives, conservation at Rushikulya rookery has witnessed remarkable success. Community-led initiatives, educational programs, and digital communication platforms have facilitated effective monitoring, hatchling guidance, and awareness campaigns, fostering environmental stewardship among stakeholders. The record-breaking mass nesting of over 900,000 turtles in 2025 underscores the significance of these efforts. This research highlights the impact of participatory communication in mobilising and empowering conservation stakeholders, analysing key communication tools and techniques. By integrating indigenous knowledge and fostering a sense of ownership, participatory conservation approaches can enhance ecological outcomes and ensure the survival of Olive Ridley turtles for future generations. The study provides insights into scaling and replicating participatory communication strategies to address broader conservation challenges effectively.